The Protective Effect of a Newly Developed Molecular Chaperone- Inducer Against Mouse Ischemic Acute Kidney Injury - Worapat Prachasilchai; Hiroko Sonoda; Naoko Yokota-Ikeda; Katsuaki Ito; Takashi Kudo; Kazunori Imaizumi; Masahiro Ikeda (Elsevier, 2009)
Activation of the unfolded protein response (UPR) has been suggested to attenuate renal ischemia-reperfusion (I/R) injury. We recently found a compound, namely BIX, that activated the UPR selectively through the activating transcription factor 6 pathway. This study examined the effect of BIX on renal I/R injury in mice. BIX selectively up-regulated renal BiP mRNA and protein. Pretreatment with BIX significantly ameliorated renal I/R injury. Coadministration of BIX and tunicamycin, a non-selective UPR inducer, provided no additional protection. Our results suggest that the UPR activation by BIX leads to a novel drug therapy against renal I/R injury. Keywords:: renal ischemia-reperfusion injury, endoplasmic reticulum (ER) stress, unfolded protein response